2019
DOI: 10.1111/pbi.13096
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking natural polymorphism in eIF4E by CRISPR‐Cas9 base editing is associated with resistance to potyviruses

Abstract: Summary In many crop species, natural variation in eIF 4E proteins confers resistance to potyviruses. Gene editing offers new opportunities to transfer genetic resistance to crops that seem to lack natural eIF 4E alleles. However, because eIF 4E are physiologically important proteins, any introduced modification for virus resistance must not bring adverse phenotype effects. In this study, we assessed the role of amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 82 publications
1
101
0
Order By: Relevance
“…Here, we show for the first time that PPE2 strategy developed for dicot species is able to edit an endogenous gene in the cultivated tetraploid potato. Compared to our previous work on cytosine base editing in potato and Arabidopsis (Bastet et al, 2019;Veillet et al, 2019b;Veillet et al, 2019a;Veillet et al, 2020), the efficiency of our PPE strategy appears to be limited, as already observed for cereals. Once improved, the prime editing technology, by largely expanding the range of targeted base substitutions, could make precision breeding amenable in polyploid and vegetatively propagated crops such as potato.…”
Section: Resultsmentioning
confidence: 67%
“…Here, we show for the first time that PPE2 strategy developed for dicot species is able to edit an endogenous gene in the cultivated tetraploid potato. Compared to our previous work on cytosine base editing in potato and Arabidopsis (Bastet et al, 2019;Veillet et al, 2019b;Veillet et al, 2019a;Veillet et al, 2020), the efficiency of our PPE strategy appears to be limited, as already observed for cereals. Once improved, the prime editing technology, by largely expanding the range of targeted base substitutions, could make precision breeding amenable in polyploid and vegetatively propagated crops such as potato.…”
Section: Resultsmentioning
confidence: 67%
“…The detection of specific homozygous variants in the natural pool can guide genome editing projects in targeting the “naturally” occurring mutations. This “tailored gene editing” mimicking natural polymorphisms, has been recently demonstrated by Bastet et al (2017; 2019). Moreover, breeding programs could take advantage of the information on homozygous and heterozygous selected mutations of S-genes in a next-generation marker-assisted breeding program.…”
Section: Resultsmentioning
confidence: 92%
“…Here we presented the first report to our knowledge of gene-editing using Cas9 in a nut crop. The versatility of CRISPR-Cas9 tools goes beyond point mutations adjacent to PAM sites, with options in base-editing variations already employed in some crops (Bastet et al, 2019;Wu et al, 2019). When used in combination, multiple sgRNAs targeting the same exon or different exons within the same gene provide a higher chance of a functional knockout (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%